From adolescence to old age: how sensory precision shapes body ownership during physiological aging - Martinelli, Isabella; Risso, Gaia; Bertoni, Tommaso; Meregalli, Valentina; Collantoni, Enrico; Molteni, Franco; Pedrocchi, Alessandra; Bottini, Gabriella; Serino, Andrea; Bassolino, Michela (Frontiers in Human Neuroscience, 2025)
Body ownership relies on the integration of multisensory signals coming from the environment and the body itself. Considering the substantial neurophysiological and sensory modifications occurring across the lifespan, this study aims to quantitatively evaluate age-related changes in hand ownership and its underlying bottom-up sensory and top-down components from adolescence to advanced aging. Ninety-two healthy women aged 15–83 underwent a virtual-reality based visuo-proprioceptive disparity task in which they performed reiterative reaching movements towards visual targets while observing a virtual-hand that could be spatially congruent or displaced at different disparities from the real hand’s position. Ownership was assessed by collecting reaching errors (implicit) and asking ownership judgments toward the virtual-hand (explicit). Errors were modeled using a Bayesian Causal Inference framework in which ownership for the virtual-hand resulted from a weighted average between pure visual and pure proprioceptive guidance according to their relative precision (i.e., bottom-up sensory components), and to the a priori probability that the virtual-hand was one’s own (i.e., top-down prior). Results showed that both explicit and implicit ownership towards spatially incongruent virtual-hands was higher with advancing age. Moreover, the sensory components extracted from the model revealed higher proprioceptive and lower visual variability in older adults, suggesting that as proprioception declines, visual input increasingly assumes a dominant role. No age-effect was found on the prior (i.e., top-down component). We concluded that ownership progressively changes from adolescence to old age, mostly driven by a physiological reduction in proprioceptive abilities. The sensory recalibration toward visual reliance might reflect a compensatory mechanism to maintain coherent body ownership despite age-related sensory decline.